Peran Gerakan Mengajar Desa (GMD) dalam Membangun Modal Sosial Siswa di Desa Sedong Lor Kabupaten Cirebon - Salsabila Belva Fithriyah; Dasim Budimansyah; Dede Iswandi (Lembaga Pengembangan Kinerja Dosen, 2025)
The low level of active student participation in rural learning environments poses a significant challenge to the education system. This study aims to examine the role of Gerakan Mengajar Desa (GMD), a community-based non-formal education initiative, in fostering students’ social capital at SD Negeri 1 Sedong Lor, Cirebon Regency. Employing a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles & Huberman’s interactive model. The findings reveal that the GMD program significantly enhances students’ self-confidence, social interaction, and active engagement in collaborative learning activities. Through contextual and participatory learning methods, GMD cultivates essential social values such as mutual cooperation, empathy, responsibility, and teamwork. These findings highlight GMD’s effectiveness as a transformative model for strengthening student character and building social capital in areas where formal education access remains limited.